Structure and Electrochemical Impedance of LiNi\(_{x}\)Mn\(_{2 - x}\)O\(_{4}\) - Anh Tan, Ta; Si Hieu, Nguyen; Ha Chi, Le; Tran Chien, Dang; Dinh Trong, Le; Duy Long, Pham (Communications in Physics, 2017)
Ni-substitution spinel LiNixMn2−xO4 (x = 0, 0.1, 0.2) materials were synthesized by the sol--gel method. The structure and  morphology of the samples were characterized by the X-ray diffraction (XRD)  and the scanning electron microscopy. The ac conduction of the materials was  investigated by electrochemical impedance spectroscopy (EIS) measurements.  The refinement results showed that the substitution of Ni decreased the  lattice constant and Mn--O distance, while increased Li--O bond length and  16c octahedral volume. The EIS results confirmed the decrease of  conductivity with increasing Ni substitution content. Based on XRD and EIS  results, the relationship between the crystal structure and electrochemical  behavior of the materials was discussed and explained.